PRODUCT DEVELOPMENT IN THE CONCEPT OF ECOLOGICAL MARKETING - Koreleska, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2009)
The aim of this paper is to present the ecological product and the possibilities of its development in the process of ecological marketing. Ecological marketing is a modern concept of social marketing, which takes into consideration the three subjects of the exchange process, i.e. the producer, the consumer and the society as a whole. The individual research was conducted among the owners or executives of the food-processing plants (an individual and direct interview). The researchers described and evaluated et. al the target market of the companies, the exploited sources of information concerning the consumers, the assortment, the factors deciding about the launching of new products and product strategies. The researched entrepreneurs are able to define accurately the target market and their choice of the information sources is appropriate. The straight majority of the companies are very innovative, which is being constantly proven by the launching of new products. The majority of the companies conduct consumer research randomly, which may be less beneficial for these companies in the future.